Perlindungan Hukum Pemegang Hak Cipta atas Film Impor - Agus Wasita (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Since the enforcement of Law No. 19 Year 2002 on Copyright, in particular film businessmen greatly expect that the government may protect the holders of copyright on films, either domestic produced films or imported films against the practice of film pirating. To improve effectively the protection of copyright, since 29th day of July 2003, the Directorate General of Intellectual Property Right (HAKI) of the Ministry of Justice and Human Rights has appealed shopping centers not to provide any single place for businessmen to sell pirated goods. But the appeal looks running ineffectively, because no legal force being imposed to provide certainty, however the Directorate General of HAKI of the Ministry of Justice and HAM (Human Rights) issued threatening of criminal sanction or civil compensation if the Mall/Plaza management still make any violation on the provisions of prohibition to provide any single place for selling the pirated goods. The arising loss resulted from film pirating actually not only suffers a financial loss for the film businessmen but also the state in this case procured from the tax sector. According to Kompas, the state at least suffered financial loss of 11 trillion as from 2005 procured from value added tax which should be levied by the state of film and song sales. additional information this business scale of pirated films may achieve the turnover of Rupiah billions weekly. It can be imagined what will be made by the perpetrators of film pirating in order that their illegal businesses are not disrupted. However, since the 80s the issue on law enforcement, particularly in upholding and handling the copyright has never been seriously handed and completed. The issue on both parallel import and violation of Law No. 8 of 1992 likewise, especially with regard to the obligation to censor film can not be handled appropriately. Meanwhile, the holders of copyright great do hope the police institution may directly arrest the perpetrators of pirating and processes them until filing claims. But apparently from the cases handled, which may further be processed until filing the claims are some of them only. By virtue of above illustration, the prominent issue to be discussed in this writing is ineffectiveness of legal enforcement of the state against the holders of copyright of imported films. It is alleged for insufficient statutory regulations to solve the complicated problems, obscure rule of games and the officers of legal institution weakly apply the law enforcement.